PERCEPTION-BASED EVALUATION OF URBAN PUBLIC SPACES IN DELHI: A MULTI-DIMENSIONAL FRAMEWORK FOR ASSESSING CHALLENGES AND OPPORTUNITIES ACROSS FIVE TYPOLOGICALLY DISTINCT SITES - Vats, Simran; Singari, Ranganath M (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Urban public spaces are indispensable to social, ecological and cultural life of the city, but their experiential quality is assessed in an inconsistent manner, more so in the quickly growing metropolises like Delhi. Delhi is one of the most densely populated urban conglomerations in the world and the capital of the country, making it a complex city with a variety of public space typologies, socio-spatial dynamics, heritage contexts and user demographics. This study involves the development and validation of a multi- dimensional perception-based evaluation framework of urban public spaces, which is tested in an empirical study of five typologically diverse urban public spaces in Delhi: Sarojini Nagar Market (commercial stretch), Rajiv Chowk (transit hub), Mehrauli Archaeological Park (heritage space), Lodhi Garden (green space), and Connaught Place (civic plaza). The framework is based on user experience (UX) design methods, environmental psychology and urban design theory, and incorporates four evaluative dimensions: (1) Spatial Quality, (2) Accessibility and Inclusivity, (3) Ecological and Environmental Comfort, and (4) Socio-Cultural Vitality. A validated 38 item questionnaire was used to collect data from 500 respondents at all five sites, systematic behavioral observation was conducted using an adapted SOPARC protocol, and GIS based spatial analysis was employed. A 3-D Importance- Performance Analysis (IPA) is a diagnostic tool model identified the critical design gaps that included Accessibility and Inclusivity (mean gap: -2.36) and Ecological Comfort (mean gap: -1.49), and showed high degree of variance across sites and across demographics. The resulting framework provides a replicable diagnostic tool for Indian urban planners, designers and policy makers that can be directly applied to the Smart Cities Mission, AMRUT 2.0, and SDG 11 targets, and is grounded in the context of India.